Arts Management, Cultural Policy, & the African Diaspora - Cuyler, Antonio C. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book centers people of African descent as cultural leaders to challenge the myth that they do not know how or care about managing and preserving their culture. Arts Management, Cultural Policy, & the African Diaspora also presents comparative case studies of the challenges, differences, similarities, and successes in approaches to cultural leadership across multiple cultural contexts throughout the diaspora. This volume disrupts the enduring and systemic global marginalization, oppression, and subjugation that threatens and undermines people of African descent's cultural contributions to humanity. The most important distinguishing feature of the volume is its geographical use of the African diaspora to explore the subjects of arts management and cultural policy which, to date, no volume has done before. Furthermore, the volume's comparative examination of ten critical, historical, practical, and theoretical questions makes it a significant contribution to the literatures in Arts Management, Cultural Policy, Cultural, Africana, African American, and Ethnic studies. Dr. Antonio C. Cuyler is the author of Access, Diversity, Equity, and Inclusion in Cultural Organizations: Insights from the Careers of Executive Opera Managers of Color in the US (2020). He is the Director & Associate Professor of Arts Administration at Florida State University (FSU), Visiting Associate Professor of Theatre & Drama in the School of Music, Theatre & Dance at the University of Michigan, and the Founder of Cuyler Consulting, a Black-owned arts consultancy which helps cultural organizations maximize their performance and community relevance through access, diversity, equity, and inclusion (ADEI).
1. Towards an effective cultural policy in the Republic of Benin, Espéra Donouvossi -- 2. From Passion to Profession: Shaping the Future of Arts and Culture in Botswana, Moletedi One Ntseme -- 3. Cultural Policy and the Film Sector in Cameroon, Dr. Alasambom Nyingchuo -- 4. Arts Management and Cultural Policy in Ghana, Amos Darkwa -- 5. Ghana's Cultural Policy and (Dis)Empowerment: A Three-Decade's Reflections on the Centres for National Culture (CNC), Eyram E. K. Fiagbedzi and Richardson Commey Fio -- 6. Cultural responsiveness in communities of practice, institutions, and corporations as a result of cultural policy transformation in Kenya, Dr. Patricia Opondo -- 7. Systematization of culture: Public and Private Interventions in Nigeria's contemporary art system, Jonathan Adeyemi -- 8. Cultural Patrimony and Discussion of the 1897 Invasion of Benin Kingdom: Some Questions for Arts Management, Dr. Ezeluomba Ndubuisi -- 9. Tunisian Cultural Policy: Perspectives and challenges of a state's project, Alla Al Khalah & Iyadh El Kahla -- 10. Arts Management and Cultural Policy in South Africa: Navigating the Multicultural Labyrinth, Dr. Patrick Ebewo.
Keywords: Ethnology-Africa.; Culture; Cultural property; Art-History.; Emigration and immigration; African Culture; Cultural Heritage; Art History; Diaspora Studies